Fulminant heart failure due to giant cell myocarditis affecting the left ventricle - Senderek, Tomasz; Małecka, Barbara; Ząbek, Andrzej; Rudnicka-Sosin, Lucyna; Wierzbicki, Karol; Przybyłowski, Piotr; Bednarek, Jacek; Lelakowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
A 56-year-old woman, previously healthy, was hospitalized after an episode of ventricular tachycardia in the course of infection. In view of the fulminant course of heart failure the patient was connected to an extracorporeal membrane oxygenation (ECMO) system. After 3 weeks of treatment with ECMO the patient received a heart transplant. A histopathological examination of the tissues of the explanted heart revealed giant cell myocarditis. The patient was treated with immunosuppression based on induction therapy followed by a standard regimen with steroids. Currently, the patient remains in good general condition with an left ventricular ejection fraction of 60%.